Analisis Pengembangan Service Excellent dan High Quality Product Dalam Upaya meningkatkan Kepuasan Pelangan Kopi Kenangan Tamini Square - Noviana Nur Arifah; B Syarifuddin Latif (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the development of excellent and high quality service in increasing customer satisfaction at Kopi Kenangan Tamini Square. This research uses qualitative methods as well as interviews with informants, observation, distributing closed questionnaires, and documentation. The results of this research are that good service and product quality contributes significantly to customer satisfaction and building good relationships with them. Recommended strategies include continuous innovation in products and services, strengthening relationships with customers, training and development of human resources, and collecting customer feedback. Based on the SWOT analysis, strategies are recommended to utilize the company's internal strengths and overcome existing weaknesses, thereby increasing the company's competitiveness in the market